2021
DOI: 10.1109/access.2021.3112940
|View full text |Cite
|
Sign up to set email alerts
|

Relaying in the Internet of Things (IoT): A Survey

Abstract: The deployment of relays between Internet of Things (IoT) end devices and gateways can improve link quality. In cellular-based IoT, relays have the potential to reduce base station overload. The energy expended in single-hop long-range communication can be reduced if relays listen to transmissions of end devices and forward these observations to gateways. However, incorporating relays into IoT networks faces some challenges. IoT end devices are designed primarily for uplink communication of small-sized observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…Incentivized relaying in communication networks is a method proposed and studied in the literature to enable cooperative communication and forwarding in specific application networks [1]. It has potential applications in IoT networks, future cellular networks, smart cities, smart homes, wearable devices, and smart grids, where multi-hop mesh network architectures can enhance network spectral and energy efficiencies [2].…”
Section: Introductionmentioning
confidence: 99%
“…Incentivized relaying in communication networks is a method proposed and studied in the literature to enable cooperative communication and forwarding in specific application networks [1]. It has potential applications in IoT networks, future cellular networks, smart cities, smart homes, wearable devices, and smart grids, where multi-hop mesh network architectures can enhance network spectral and energy efficiencies [2].…”
Section: Introductionmentioning
confidence: 99%
“…The relay technique can expand the transmission distance and improve the transmission reliability of the system. Integrating relay and cognitive techniques can further improve the transmission performance of the system [10,11]. In [12], the closed-form expression of outage probability for a cognitive multi-hop relay network is derived over Rayleigh fading channels, and an optimization problem to minimize the outage probability of the cognitive relay network is formulated and solved.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested that clustering is one of the prominent solutions to reduce the energy consumption of the network [6][7][8][9] . Clustering reduces the interchange of redundant messages among the SNs by conserving the communication bandwidth [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy, the CH accumulates the data from SNs and sends them to the sink node. However, CHs near the sink node may experience considerable energy consumption and rapid energy depletion, which can lead to hotspots in the network [8,9] . One of the potential strategies to prevent the hot spot problem is uneven clustering, which results in varying cluster sizes with respect to the distance between the sink node and CHs; i.e., as distance increases, the cluster size also increases.…”
Section: Introductionmentioning
confidence: 99%